Discrepancy between frequent occurrence of COVID‐19‐like symptoms and low seroconversion rates among healthcare workers. Issue 3 (18th October 2021) - Dehnen, Dorothea; Dehnen, Katja; Trilling, Mirko; Fiedler, Melanie; Drexler, Julia; Goralski, Marcel; Le‐Trilling, Vu Thuy Khanh; Schöler, Lara; Jöckel, Karl‐Heinz; Heßbrügge, Martina
Abstract: During the first wave of the pandemic, we compared the occurrence of subjectively experienced COVID‐19‐like symptoms and true severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) seroconversion rates among medical personnel in general practices. This cross‐sectional study determined the SARS‐CoV‐2‐specific immunoglobulin G (IgG) antibody status of medical staff from 100 outpatient practices in Germany. Study cohort characteristics and COVID‐19‐like symptoms were obtained by questionnaires. The initial screening for SARS‐CoV‐2‐recognizing antibodies was performed using a commercial chemiluminescence microparticle immunoassay. Positive results were controlled with another approved test. Samples with discrepant results were subjected to a third IgG‐binding assay and a neutralization test. A total of 861 participants were included, 1.7% ( n  = 15) of whom tested positive for SARS‐CoV‐specific IgG in the initial screening test. In 46.6% ( n  = 7) of positive cases, test results were confirmed by an independent test. In the eight samples with discrepant results, neither spike‐specific antibodies nor in vitro neutralizing capacity were detectable, resulting in a genuine seroprevalence rate of 0.8%. 794 participants completed the questionnaire. Intriguingly, a total of 53.7% ( n  = 426) of them stated episodes of COVID‐19‐like symptoms. Except for smell and taste dysfunction, there were no significant differences between the groups with and without laboratory‐confirmed SARS‐CoV‐2 seroconversion. Our results demonstrated that only 0.8% of participants acquired SARS‐CoV‐2 even though 53.7% of participants reportedly experienced COVID‐19‐like symptoms. Thus, even among medical staff, self‐diagnosis based on subjectively experienced symptoms does not have a relevant predictive value.